Proceedings of the 15th ACM/IEEE-CS Joint Conference on Digital Libraries 2015
DOI: 10.1145/2756406.2756969
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing User Requests for Anime Recommendations

Abstract: Anime is increasingly becoming recognized as an important commercial product and cultural artifact. However, little is known regarding users' information needs and behavior related to anime. This study specifically attempts to improve our understanding of how people seek anime recommendations. We analyzed 546 user questions in natural language, collected from a Korean Q&A website Naver Knowledge-iN, where users are asking for anime recommendations. The findings suggest the importance of establishing robust met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 7 publications
2
7
1
Order By: Relevance
“…The identified codes were compared, contrasted, and merged into a single list. Analysis showed some identified codes had similarities with previous studies by Lee et al (2015Lee et al ( , 2017. Where appropriate, codes representing concepts analogous to those studies were labeled the same way for consistency.…”
Section: Methodssupporting
confidence: 80%
See 1 more Smart Citation
“…The identified codes were compared, contrasted, and merged into a single list. Analysis showed some identified codes had similarities with previous studies by Lee et al (2015Lee et al ( , 2017. Where appropriate, codes representing concepts analogous to those studies were labeled the same way for consistency.…”
Section: Methodssupporting
confidence: 80%
“…Prior studies provide some basic information about anime user needs. For instance, Lee et al (2015) analyzed recommendation questions in a Korean online anime Q&A community to identify the primary features of anime described by users. The authors found 13 prominent features: genre, title, mood, story, series, style, character, audience, length, scene, temporal, character name, and format.…”
Section: Relevant Researchmentioning
confidence: 99%
“…In a previous study on investigating anime users' information needs for recommendations (Cho et al 2017), genre was one of the most frequently mentioned features used to get recommendations (ranked third among nineteen features identified). Lee, Shim, and Jett (2015) also had similar findings: genre was the second https://doi.org/10.5771/0943-7444-2020-1-13 Generiert durch IP '44.224.250.200', am 03.11.2020, 14:49:22. Das Erstellen und Weitergeben von Kopien dieses PDFs ist nicht zulässig.…”
Section: Introductionmentioning
confidence: 57%
“…The inadequacies of existing bibliographic models when applied to more niche formats and media are a common theme in some research on entities in popular culture. Studies that have focused on video games and anime (Jett, Sacchi, Lee, & Clarke, 2016;Lee, Shim, & Jett 2015) have found that models such as FRBR are unable to adequately portray the complex relationships between these resources and also fail to provide a level of description that sufficiently addresses user requirements. These studies emphasized the need for more detailed metadata to describe features such as genre, as these are deemed by users to be vital for search and discovery.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These studies emphasized the need for more detailed metadata to describe features such as genre, as these are deemed by users to be vital for search and discovery. Lee, Shim, and Jett (2015) performed a user study of fans of Japanese anime and noted the need for more descriptive metadata, including genre, art style and character types. Similar findings were reported by Kiryakos and Sugimoto (2015) and Kiryakos, Sugimoto, Nagamori, and Mihara (2016), who found that the incorporation of data from fan pages or other hobbyist Web resources, which were at different levels of granularity, could better meet the level of detail that users of popular culture materials required.…”
Section: Literature Reviewmentioning
confidence: 99%